1982
DOI: 10.2323/jgam.28.389
|View full text |Cite
|
Sign up to set email alerts
|

Cellular fatty acid and fatty aldehyde composition of rumen bacteria.

Abstract: The genera of sixty-three bacterial strains isolated from bovine rumen contents were determined according to the identification schemes of Hungate, and Bergey's Manual of Determinative Bacteriology (8th Ed.). Then, the cellular fatty acid and aldehyde composition of all these organisms was analyzed by gas-liquid chromatography, gas chromatography-mass spectrometry, and mass fragmentography. The distinctive features of these organisms were presented. Succinivibrio contained 18: 1 (w-7), 16: 0, 14:0,16: 1, and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 9 publications
3
46
0
Order By: Relevance
“…Bacterial lipids have a high proportion of branchedchain fatty acids, synthesized from propionate and/ or volatile branched-chain fatty acid derivatives of branched-chain amino acids and plasmogenic lipids, which have DMA (MIYAGAWA, 1982;VLAEMINCK et al, 2006). The presence of DMA indicates a pattern of rumen fermentation, in which the diet is the main determinant of ruminant meat quality (ALVES et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial lipids have a high proportion of branchedchain fatty acids, synthesized from propionate and/ or volatile branched-chain fatty acid derivatives of branched-chain amino acids and plasmogenic lipids, which have DMA (MIYAGAWA, 1982;VLAEMINCK et al, 2006). The presence of DMA indicates a pattern of rumen fermentation, in which the diet is the main determinant of ruminant meat quality (ALVES et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, despite the fact that L. fermentum maintains a fermentative metabolism under aerobic conditions (Buchanan & Gibbons, 1974;Condon, 1987), oxygen has an important effect on metabolism related to membrane structure and function. No cyclic fatty acids were detected in obligately anaerobic rumen lactobacilli (Miyagawa, 1982). The induction of oleic acid synthesis might be related to the protection of the cells against the deleterious effects of oxygen.…”
Section: The Roles Of Cyclic Fatty Acids and Oxygen In Temperature Admentioning
confidence: 93%
“…It has been reported that the variation in the cellular fatty acid composition among strains belonging to the same species was relatively small with some exceptions (6,15).…”
Section: Discussionmentioning
confidence: 99%